SIFAT PEMESINAN JENIS KAYU JAWA BARAT - Osly Rachman; Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
This paper presents the result of test on machining properties of 28 wood species from Bogor and Sukabumi, West Java. The test method used was the modified ASTM D-1666 described in the Forest Products Research Institut Report No. 160 (1982). The samples (25 pieces/species) were dried to equilibrium moisture content condition (15 to 18%). The machining properties investigated were planning, shaping, boring, mortising, turning and sanding.The species that have good or very good machining properties are kobari, pasang jambe, pasang beureum, mahoni daun lebar, pentadesma, cloropora, eucalyptus, meranti batu, pinus I, mahoni, mahagoni and pinus III. Species such as kelumpang, entorolobium and cecropia are consistenlly poorer. The other species are good in some properties and fair or poor in others.